Simple to complex: keys to musical growth in a high school band class - Monical, Nancy (Kansas State University, 2019)
In the spring of 2019, I implemented a study of key signatures with my high school band to create better theoretical musical understanding amongst my students and create opportunities for individual technical improvement. The goal was to have each student create a personal relationship with every key signature, starting with sound and experience first and notation later. We started with 3 keys: one flat, one sharp, and no flats or sharps. Each week we would add one more flat and sharp to our key signatures. To demonstrate their understanding of a key, students would perform a key signature’s major, natural minor, harmonic minor and melodic minor scales without looking at musical notation. The process of getting my master’s degree has helped me to continue to grow and change as a music educator over time. It has pushed me out of my comfort zone and helped me take risks. I have added more compositional elements to my classes at all levels. I also took a hard look at my literature selections for my concert group. I was empowered to go look for composers outside the mainstream publishers and found great original works for my group to perform that created conversations about musical styles, and the history of concert bands. The creation of my personal music teaching theory helped clarify and solidify my teaching practice grades 5-12. I have a clear purpose to my methodology that is grounded in solid educational theory and experiences beyond my own classroom walls.
Keywords: Music; Band; Secondary Education